Photoluminescence of the Eu-doped thin film heterojunction GaAs/SnO2 and rare-earth doping distribution - Bueno, C. F. [UNESP]; Scalvi, L. V. A. [UNESP]; Saeki, M. J. [UNESP]; Li, M. S. (Iop Publishing Ltd, 2015)
Tin dioxide (SnO2) thin films doped with Eu3+, are deposited by the sol-gel-dip-coating process on top of GaAs films, which is deposited by resistive evaporation on glass substrate. This heterojunction assembly presents luminescence from the rare-earth ion, unlike the SnO2 deposition directly on a glass substrate, where emissions from the Eu3+ transitions are absent. The Eu3+ transitions are clearly identified and are similar to the observation on SnO2 pressed powder (pellets), thermally treated at much higher temperatures. However, in the form of heterojunction films, the Eu emission comes along a broad band, located at higher energy compared to Eu3+ transitions, which is blue-shifted as the thermal annealing temperature increases. The size of nanocrystallites points toward quantum confinement or electron transfer between oxygen vacancies, originated from the disorder in the material, and trivalent rare-earth ions, which present acceptor-like character in this matrix. This electron transfer may relax for higher temperatures in the case of pellets, and the broad band is eliminated.